Aerodynamics in sports technology - Tennis science
Tennis Science Book Table of Contents Tennis Science: The Court and Equipment - The Tennis Court - The Tennis Ball - The Tennis Racquet Basic Aerodynamics - Air is a Fluid - How Air Moves - Aerodynamics - Pressure - Density - Velocity - Acceleration - Viscosity - Friction - Boundary Layers - Laminar,Turbulence, Transition and Flow - Separation - Science Laws for Flight Forces - Weight - Lift - Magnus Effect - Thrust - Differences for Wings and Balls - Drag Ball Physics: Coefficients of Friction and Restitution Biomechanics - The Technology: Motion Capture and Analysis - Wind Tunnel - CFD